Machine tool capability profiles for representing machine tool health. (August 2015) - Vichare, Parag; Nassehi, Aydin; Thompson, James; Newman, Stephen T.; Wood, Fiona; Kumar, Sanjeev
Abstract: Control charts at present are used to provide statistical representation of machine tool health. These charts are based on machine tool testing standards, for example ISO 230, ASME B5.54 and VDI 3441, and can be utilised to decide a particular resource׳s level of utilisation during manufacturing execution. Although these standards provide an indication of machine tool accuracy, they do not provide any mechanism to exchange and use health information within these control charts to identify whether a particular machine is performing to the desired level of capability and whether that machine is healthy. It is only after control charts are manually interpreted, that machine tool selection decisions can be made. This paper reports research that exploits and extends an ISO 14649 (STEP-NC) Part 201 and Part 200 series (Machine Tool Data Model) for representing machine tool health data. This provides a new approach for representing statistical machine tool accuracy information while maintaining the compliancy within prevalent machine tool testing standards. A data model for representing machine tool health based on capability profiles has been proposed. A case study of machine tool showing the interpretation of a control chart with proposed data model has been utilised to represent machine tool health through capability profiles. Highlights: A data model for exchanging machine tool health information is proposed. Manufacturing resource capability profiles can represents state of the machine tool. Machine tool health data is stored and exchanged with ISO 10303 part-21 file format. Machine tool technological specifications are connected to the health information. Standardised machine tool health information offer interoperability advantages.